2019
DOI: 10.1136/bmjopen-2019-030564
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the efficacy of Internet-Based Exercise programme Aimed at Treating knee Osteoarthritis (iBEAT-OA) in the community: a study protocol for a randomised controlled trial

Abstract: IntroductionKnee osteoarthritis (OA) is the most common joint disease worldwide. As of today, there are no disease-modifying drugs, but there is evidence that muscle strengthening exercises can substantially reduce pain and improve function in this disorder, and one very well tested physiotherapy protocol is the ‘Better Management of Patients with Osteoarthritis’ developed in Sweden. Given the high prevalence of knee OA, a potentially cost-effective, digitally delivered approach to treat knee OA should be tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 95 publications
0
10
0
Order By: Relevance
“…The Internet-Based Exercise Programme Aimed at Treating Knee Osteoarthritis (iBEAT-OA) is a parallel-group randomized clinical trial, performed in the primary care setting and managed from Nottingham City Hospital, Nottingham, United Kingdom, in participants with knee osteoarthritis, JAMA Network Open | Orthopedics comparing a digitally delivered intervention with usual care self-management randomized in a 1-to-1 ratio. The trial protocol has been published elsewhere 13 and can be found in Supplement 2.…”
Section: Trial Designmentioning
confidence: 99%
“…The Internet-Based Exercise Programme Aimed at Treating Knee Osteoarthritis (iBEAT-OA) is a parallel-group randomized clinical trial, performed in the primary care setting and managed from Nottingham City Hospital, Nottingham, United Kingdom, in participants with knee osteoarthritis, JAMA Network Open | Orthopedics comparing a digitally delivered intervention with usual care self-management randomized in a 1-to-1 ratio. The trial protocol has been published elsewhere 13 and can be found in Supplement 2.…”
Section: Trial Designmentioning
confidence: 99%
“…The cohorts included a subset of the KPIC cohort (n = 129), 92 participants from the iBEAT-OA cohort, and a third cohort with 62 participants (Supplementary Table 1). Baseline pain data from the iBEAT-OA cohort (25) used in this study included quantitative sensory testing measurement of PPTs, temporal summation, and conditioned pain modulation. In the third cohort of 62 individuals with radiographic knee OA (24), participants were asked if they were currently experiencing knee pain at the time of blood donation, and pain was assessed using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) (26).…”
Section: Methodsmentioning
confidence: 99%
“…Baseline serum samples from the Internet-Based Exercise Programme Aimed at Treating Knee Osteoarthritis (iBEAT-OA) cohort study (n = 94) were used as age-and sex-matched SARS-CoV-2-negative controls [31]. As these samples were collected prepandemic, a lack of SARS-CoV-2 infection was not confirmed.…”
Section: Sample Collection and Preparationmentioning
confidence: 99%